A generic approach for mechano-chemical reactions between carbonnanotubes of different functionalities. (August 2016) - Kabbani, Mohamad A.; Tiwary, Chandra Sekhar; Som, Anirban; Krishnadas, K.R.; Autreto, Pedro A.S.; Ozden, Sehmus; Keyshar, Kunttal; Hackenberg, Ken; Chipara, Alin Christian; Galvao, Douglas S.; Vajtai, Robert; Kabbani, Ahmad T.; et al.
Abstract: Here, we report similar reactions between nanotubes carrying functionalities, namely carbon nanotubes (CNTs) with the acyl chloride/hydroxyl and amine/carboxylic functionalities directly attached to their surfaces, resulting in the formation ofchemically modified graphene products. The reaction is spontaneous and is facilitated by simple grinding of the reactants. The new solid-state reactions have been confirmed using different spectroscopic and electron microscopy techniques.